Closing the Loop Valorization of Industrial Waste of Composite Materials through Re-Design of Products from Detached Value Chains. (May 2022) - Cappelletti, F.; Rossi, M.; Germani, M.
Abstract: The literature lacks methodologies to make supply chains of composite materials circular. The proposed approach aims to transform scraps and off-specification products into secondary raw materials. Its novelty is to find innovative applications, instead of re-introducing scraps in the loop they come from. The case study investigates how scraps can be re-worked and re-used as raw material. First, the processes are analyzed; some components are then re-designed to be made of the discarded scraps (composites material). Results reveal that the symbiosis can ensure green, high performing products.